PERAN KEPALA SEKOLAH DALAM PROGRAM PENGEMBANGAN KINERJA GURU - Vitorynie, Irnie; Nurwahid, Muhammad Salman; Fahrezi, Muhammad Adnan (Universitas Muhammadiyah Tapanuli Selatan, 2024)
An option to increasing potency is education. Education affects a nation's development and is crucial in raising the calibre of its human resource base. An individual's knowledge and abilities can be improved through education, making them more qualified and anticipated to be able to expand their perspectives, open their minds, and become proficient with IPTEK in order to advance national development. In addition to being a crucial component of education, teacher effectiveness also determines the overall quality of education. Teachers evaluate themselves based on how well they execute their responsibilities as instructors. The quality of a teacher's performance impacts the value of the educational outcomes that students receive because teachers are the ones that contact with students most directly during the learning process.The researchers have gathered qualitative data. (talking head). It is the study of how words or language function in a certain environment in a methodical fashion using scientific methods in order to gain a comprehensive understanding of the phenomena that a subject is experiencing, such as behaviour, perception, motivation, thinking, and action.The study's findings indicate that the principal plays a crucial role in implementing the Master Performance Improvement Programme as an EDUCATOR, MANAGER, and MOTIVATOR.